Potential benefits of dry direct seeded rice culture: A review - Rahman, Md Moshiur (Fundamental and Applied Agriculture, 2019)
Puddled transplanting is the major system of rice cultivation in many parts of the world. Transplanting system provides a high and stable yield. It is labour intensive and requires huge amount of irrigation water (1500-2000 mm). The increasing scarcity of irrigation water and labour acted as a major driver to the adoption of the wet direct seeding system in many Asian countries. Wet direct seeding saves substantial amount of labour but it has very low water saving potential. Dry direct seeding is another rice establishment method that has potential to save both water and labour in rice culture. Seedling raising, puddling and transplanting of seedling into the puddle are omitted in the dry direct seeding system, rather primed seeds are directly sown on the dry cultivated land by hand or seeder or directly by seeder without tillage. Direct seeding contributes to saving of 50% labour requirement in crop establishment. The labour saving could be even more if seeding is done by machineries. Dry direct seeding gives comparable or even higher yield than that of puddle transplanted rice. It reduces greenhouse gas emission, buildup of arsenic and other heavy metals and improves soil health compared with the conventional system. Dry direct seeded rice based cropping system offers the scope of increasing cropping intensity and diversity and farm income. Yield decline in dry direct seeded system has been reported elsewhere and the reduction of yield was mainly related with inadequate agronomic management and under continuous mono-crop upland condition. However, trials at farmers’ field in Bangladesh proved that dry direct seeded rice can give better harvest than the conventional puddle transplanted rice with proper agronomic management. The adoption of dry direct seeded rice culture in Bangladesh is mainly constrained by the present irrigation water sharing system and unavailability of good quality seeding machineries. The present review focuses on the effect of dry direct seeded rice on water requirement, yield performance, cropping intensity and diversity, soil physical and chemical properties, greenhouse gas emission, labour and economic issue so that dry direct seeding can be used as a tool for increasing crop productivity with less water with minimal adverse effect on soil and environment.